2017
DOI: 10.1016/j.compstruct.2016.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting behaviour for aircraft composites structures using macro-fibre composite: Part I – Integration and experiment

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Abstract: This paper investigates new ways to integrate piezoelectric energy harvesting elements onto carbon-fibre composite structures, using a new bonding technique with a vacuum bag system and co-curing process, for fabrication onto airframe structures. Dynamic mechanical vibration tests were performed to characterise the energy harvested by the various integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Harvesting vibrational energy dissipated from these structures could solve these issues. To date, many energy harvesting powered structural monitoring systems have been reported, including those for asphalt pavement, oil pump, vehicle suspension, bridge, vehicle tire, railway and train, and aircraft and spacecraft . There are also plenty of comprehensive reviews discussing the topic of vibrational energy harvesting …”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…Harvesting vibrational energy dissipated from these structures could solve these issues. To date, many energy harvesting powered structural monitoring systems have been reported, including those for asphalt pavement, oil pump, vehicle suspension, bridge, vehicle tire, railway and train, and aircraft and spacecraft . There are also plenty of comprehensive reviews discussing the topic of vibrational energy harvesting …”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…MFC is lightweight, low power and can be integrated with existing aerospace composite material. This builds onto and extends beyond the previous work by one of the authors in the areas of integration of MFC into aircraft composite [24], as well as the investigation of delamination behaviour of composite materials [25], [26]. Finite element model was explored to study the mechanical vibration modes to find the maximum shear stress generated as references of experimental input.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, possible testing on scaled prototype wing model in wind tunnel will also help to validate the concept in representative conditions. Based on previous integration experience for another application [24], MFC will also be integrated into the top layer of the the composite during prepreg stage in order to validate the performance of a fully integrated composite stack. Future work will also investigate the possibility to integrate with MEMS frequency controllers [38], macro-scale [39] and MEMS [40], [41] piezoelectric vibration energy harvesting, FPGA, microcontrollers and thin film power electronics, in order to realise a low power, light weight and thin profile smart shear wave de-icing system that can be integrated into the CFRP composite stack.…”
Section: Ongoing and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the integration with composite materials, piezoelectric films are particularly suitable due to the thin profile and manufacturing compatibility [28,29]. A previous study [30] has shown experimental integration and characterisation of piezoelectric macro-fibre composite (MFC) transducers with CFRP targeted for aircrafts, especially in order to be compatible with the flexible design of aircraft wings.…”
Section: Introductionmentioning
confidence: 99%